Valorisation des collections publiques de tapis marocains au temps du protectorat français (1912-1935) - Khalid Loukid (L’Année du Maghreb)
Moroccan carpet craftsmanship was of particular interest to the French authorities from the start of the protectorate in Morocco (1912-1935). The particularities and “indigenous” character of Moroccan carpets, whether in Amazigh or Arab style, quickly attracted the interest of Resident General Hubert Lyautey and Prosper Ricard, head of the so-called Service des arts indigènes. At the time, carpet-making in Morocco was flourishing in both urban and rural areas, with production centers such as Rabat, Salé, Casablanca, Meknes, Fez and Marrakech. There was considerable regional diversity, particularly between carpets from the Middle Atlas, the High Atlas and the Haouz region of Marrakech.Thus, the protectorate authorities launched a specific crafts policy, accompanied by the creation of institutions dedicated to the management and development of the crafts sector, in particular Moroccan carpets, which benefited from a legislative framework as well as control and valorization mechanisms. The Office des industries d’art indigènes, created in 1918 and subsequently renamed Service des arts indigènes (1920), was headed by Prosper Ricard (1920-1935). This department transformed the cultural and craft sector, in particular the working methods of carpet weavers. The promulgation of the dahir (royal decree) of stamping, in 1919, outlined and completed the fundamental axes of the colonial strategy towards carpet craftsmanship, its promotion and the control of its “authenticity”.This article takes a critical look at these legislative and “renovation” measures. It examines their impact on the production, conservation, valorization and marketing of Moroccan carpets. The central hypothesis is that, while this policy has made it possible to preserve certain craft practices and promote Moroccan handicrafts internationally, it has also transformed the carpet industry into an instrument serving colonial interests. The aim is to show how the protectorate restructured carpet production while controlling its distribution and exploiting its image to consolidate its hold.Although this policy had both positive and negative effects on carpet craftsmanship, it left a lasting imprint on traditional weaving techniques in Morocco. Its impact endures to this day, influencing carpet decoration, as well as the perception and preferences of the Moroccan public distinguishing between “urban” and “rural” carpets. Morocco’s national archives and museum archives, such as those of the Dar Si Saïd museum in Marrakech with its ancient carpet collection, provide us with information on the policy adopted by Lyautey and Ricard, on the organization of craft fairs and exhibitions as tools for promoting and enhancing these products, both nationally and internationally. In addition, Le Corpus de tapis marocains (The Corpus of Moroccan Carpets) remains a benchmark in Moroccan carpet collections; its four volumes (1923-1934) are the work of Prosper Ricard.The effects of this policy on Moroccan carpet collections are varied and significant: increased and regulated production, intense international marketing and the preservation of a museum collection of indigenous art carpets serving as “models” for craftsmen. However, this policy has modified the old ways of making carpets by influencing the use of motifs to better satisfy a European clientele. Small businesses and craftsmen in general do not seem to have benefited fully from this economic dynamic.